Mobile Chinese entrepreneurs - Kwok-bun, Chan; Chan Wai-wan.; SpringerLink (Online service). (New York Springer, 2011)
From nomadic traders in the ancient world to peddlers on the American frontier, the immigrant entrepreneur is a timeless figure. In our current age of globalization and multinational corporations, however, this experience is complicated by patterns of adaptation and transformation,relocation and re-invention. Mobile Chinese Entrepreneurs draws extensively on the narratives of sixteen small-to-medium business owners, born on the mainland, who have immigrated to Hong Kong and returned to China to establish their enterprises.For these executives, business and social life alike are marked by constant interplay of identities, such as individual identity/group membership and ancestral/immigrant identity. Yet as often as this juggling of these ?selves?can be beneficial in the economic sphere, it can also lead to feelings of rootlessness and alienation. Writing with rare sensitivity, the authors synthesize insights from economic sociology, psychology, ethnic relations, and social networks, creating an exploration of social capital and social identity comparable to similar groups of businessmen and women in other areas of the world.  Among the topics examined: Life/work balance and the role of family. Transient identities: local, Hongkonger, Chinese, international. Social organizations as drivers of public and private life. Clashes between managerial generations. Ethnic businesses and government policy: prosperity, marginalization, and points in between. Mobile Chinese Entrepreneurs will interest researchers in family sociology, economic sociology, and psychology, not only those who focus on this particular population but also those seeking unique perspectives into immigrant experience.
Shuttling Nomads in Mobile Times -- Research Methodology.-Identity, Interpersonal Networking, and Enterprise Management.-Seven Vignettes -- The Spatial Triangulation of Immigrant Entrepreneurship -- Association: Mediating Self-Identities -- The Double-Edged Sword: Mobility and Entrepreneurship -- Conclusion.
Electronic reproduction.
Keywords: Internal migrants -- China -- Economic conditions; Migration, Internal -- Economic aspects; Migration, Internal -- China; Entrepreneurship -- China; Ethnicity -- China; China -- Economic conditions; Electronic books